ANALISIS KEBUTUHAN DAN KETERSEDIAAN AIR KABUPATEN MANOKWARI DENGAN MODEL MOCK - Prima Jiwa Osly; Fulki Dwiyandi; Irfan Ihsani; Rhonny Einsten Ririhena (Jurnal Infrastruktur, 2019)
Water is one of living resource, because the water is an essential substance or constituent for human’s and other living life. There is no life on earth that may last without water. If the water supply is not enough for the needs of humans and other living beings, there will be conflicts between or among them. Due to the consideration, this research is aimed to analyze how much is the of water supply pottential based on dependable flow and how much is the demand of water in Kabupaten Manokwari. The water supply in Kabupaten Manokwari is meant to fulfill the water demand in this region quantitatively. This research is using analysis by the FJ. Mock methods. FJ. Mock mmethod uses rainfall-run off model by using rainfall data, potential evapotranspiration, and characteristics hydrology for predicting the number of river discharge by the monthly period. The result of this research is shows that annual dependable flow to the possibility of fulfilled 50% is equal to Q = 178.352 (m3/det) and discharge andalan 80% is Q = 152.405 (m3/det). The potential for water supply in Kabupaten Manokwari in 2018 is 398 570 549 m3 and the total water demand for use as many as 66.629.639 m3, kabupaten Manokwari having a surplus of raw water that could be used more.